Edukasi Gizi Seimbang dan Lomba Menu Sebagai Upaya Pencegahan Triple Burden Of Malnutrion - Wijianto, Wijianto; Candriasih, Putu; Hafid, Fahmi; Kurniasari, Dian; Asomah, Nur Eli; Galonso, Nitro; Kalaha, Evelin; Tiwow, Marlin (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Adolescence is an important period in forming behavior related to health and nutrition. Decreased physical activity, eating disorders, consuming fast food from outside the home, and poor diversity of food consumption contribute to three nutritional problems (Triple Burden of Malnutrition). Poor eating habits and not having a balanced nutritional pattern will negatively impact teenagers' health and nutrition. The aim of this service is to increase teenagers' knowledge and skills about balanced nutrition through the contents of my plate and direct practice through menu competitions. The method used in this service activity goes through three stages, namely 1) Planning and preparation, 2) Education and socialization, 3) Demonstration and menu competition. This activity involved all 429 students of SLTA N 3 Luwuk. During educational and socialization activities, the material was presented about the Triple Burden of Malnutrition, balanced nutrition, and what's on my plate. The menu competition activity was attended by representatives of each class who served various dishes with a balanced and varied nutritional menu. Socialization activities and menu competitions should be carried out effectively to increase knowledge and develop character in teenagers regarding the importance of a healthy lifestyle with balanced nutrition to prevent the occurrence of the Triple Barden of Malnutrition.